Efficacy and Safety of Appetite-Stimulating Medications in the Inpatient Setting. Issue 3 (March 2019) - Howard, Meredith L.; Hossaini, Roya; Tolar, Catherine; Gaviola, Marian L.
Background: Hospitalized patients are subject to acute illness and stress which may impact appetite or weight. Loss of appetite may lead to increased morbidity or mortality. Medications such as dronabinol, megestrol, and mirtazapine are used for weight gain in the outpatient setting; however, there is limited information about safety or effectiveness when initiated inpatient.Objectives: To analyze the effectiveness and safety of appetite-stimulating medications in hospitalized patients.Methods: This was a retrospective cohort study of hospitalized patients initiated on dronabinol, megestrol, or mirtazapine for appetite. The primary outcome was change in meal intake between drug initiation and discontinuation. Secondary outcomes included documented improvement in appetite, change in weight and various laboratory parameters, and incidence of adverse effects.Results: A total of 38 patients met inclusion criteria, and mirtazapine was most commonly used (42%). There was no significant difference between groups of appetite-stimulating medications with regard to mean change in meal intake, weight, albumin, or documented improvement in diet. Within groups, each agent showed numerical improvement in percentage meal intake, with a mean change from initiation to discontinuation of 17.12%. Almost half (48%) of the patients experienced improvement in diet after the start of medications. No serious adverse effects were observed.Conclusion and Relevance: In inpatients, there was no difference in change in meal intake or weight between dronabinol, megestrol, or mirtazapine, but they may show numerical improvements in meal intake. To our knowledge, this is the first study to evaluate the use of dronabinol, megestrol, and mirtazapine initiated in the inpatient setting.